The role of the voivodeship capital cities of Eastern Poland in the aspect of stimulating regional development - Kot, Janusz; Kraska, Ewa (Rola miast wojewódzkich Polski Wschodniej w aspekcie stymulowania rozwoju regionalnego, 2019)
According to the core-periphery model, large urban centers can make peripheries dependent on them, or consolidate their advantage over the peripheries through the mechanism of polarization. This article is an attempt to verify the theories of regional development covering the influence of central areas on the development of the neighboring areas, i.e. the core-periphery theories. The article presents a study of the dynamics of development of capital cities of Eastern Poland’s regions in order to answer the question: is the development of capitals of depressed regions correlated with the dynamics of regional development processes? The research has shown that regional capitals do not play the role of voivodeship development stimulators. Therefore it can be argued that in the case of regions with a low level of socioeconomic development, the phenomenon of resource leaching occurs to a greater extent than the stimulation of development by their capital cities
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 136-151
Keywords: eastern Poland; regional development; core-periphery theories; Polska Wschodnia; rozwój regionalny; teorie centrum-peryferie